2017
DOI: 10.1590/0100-3984.2016-0123
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic pulmonary calcification: high-resolution computed tomography findings in 23 cases

Abstract: ObjectiveThe aim of this study was to evaluate the high-resolution computed tomography (HRCT) findings in patients diagnosed with metastatic pulmonary calcification (MPC).Materials and MethodsWe retrospectively reviewed the HRCT findings from 23 cases of MPC [14 men, 9 women; mean age, 54.3 (range, 26-89) years]. The patients were examined between 2000 and 2014 in nine tertiary hospitals in Brazil, Chile, and Canada. Diagnoses were established by histopathologic study in 18 patients and clinical-radiological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 35 publications
(37 reference statements)
1
32
0
Order By: Relevance
“…Corroborating the findings of previous studies, Belém et al ( 7 ) demonstrated a clear association between MPC and chronic renal failure, highlighting the strong correlation of the latter condition with cardiovascular events and the greater susceptibility to infections in immunocompromised individuals ( 1 - 4 , 7 , 8 ) . The Belém et al ( 7 ) finding of ground glass opacities—the most common pattern in their sample—broadens the range of differential diagnoses in this group of patients, including congestive conditions and infections ( 9 ) . After ground glass opacities, the most common findings were dense consolidations and calcified micronodules, which also involve multiple differential diagnoses, including other metabolic conditions, pneumoconiosis, and drug (amiodarone) toxicity ( 10 ) .…”
supporting
confidence: 75%
See 3 more Smart Citations
“…Corroborating the findings of previous studies, Belém et al ( 7 ) demonstrated a clear association between MPC and chronic renal failure, highlighting the strong correlation of the latter condition with cardiovascular events and the greater susceptibility to infections in immunocompromised individuals ( 1 - 4 , 7 , 8 ) . The Belém et al ( 7 ) finding of ground glass opacities—the most common pattern in their sample—broadens the range of differential diagnoses in this group of patients, including congestive conditions and infections ( 9 ) . After ground glass opacities, the most common findings were dense consolidations and calcified micronodules, which also involve multiple differential diagnoses, including other metabolic conditions, pneumoconiosis, and drug (amiodarone) toxicity ( 10 ) .…”
supporting
confidence: 75%
“…The number of cases included allowed the spectrum of known tomography presentations of the disease to be expanded. In some of the patients, the authors identified reticular opacities with calcified micronodules, which have not previously been reported in MPC ( 7 ) .…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…The hydroxyapatite crystals that form the chief constituent of the calcific deposits in PHPT, avidly absorb 99m Tc-MDP, thus making it a sensitive modality for diagnosis 8. HRCT of the thorax can be normal or show differing patterns of abnormalities like centrilobular ground-glass nodules, calcified nodules, localised or diffuse patchy infiltrates and vascular calcification 9. Calcification is seen in only two-thirds of the patients 10…”
Section: Discussionmentioning
confidence: 99%